Effects of statin therapy on mean platelet volume in patients with risk of cardiovascular diseases: a systematic review and meta-analysis. Issue 7 (26th July 2019) - Ji, Shuaifei; Zhang, Babo; Wang, Xianda; Shi, Heng; Yu, Lixin; Wang, Xiaocheng
Abstract : Many studies have demonstrated the effects of statin therapy on platelet, but it is controversial that whether statin could reduce mean platelet volume (MPV) in patients with the risk of cardiovascular diseases. To further improve the clinical significance of MPV in those patients and explore new function of statin, we conducted this research. Relevant studies were selected by searching electronic databases (PubMed, Embase and Cochrane Library) and reference lists of related articles by hand. Two reviewers independently assessed eligibility and quality of the studies. Eventually, we included ten studies, a total of 1189 patients with the risk of cardiovascular diseases. Consolidating relevant data and comparing the changes of MPV before and after statin treatment, we found that statin could decrease MPV [standard mean difference (SMD) = −0.47 (−0.71–0.23)], which was statistically significant ( P =0.0001). Subgroup analysis suggested that when ≥55 years, this decrease did not occur [SMD = −0.06 (−0.18, 0.06)]. Drug type, sample size, ethnicity, mean age and quality of included article were sources of heterogeneity. Therefore, statin therapy could reduce MPV significantly and exhibited antiplatelet activity, which is of great importance in clarifying the clinical significance of MPV in cardiovascular events and the prevention of cardiovascular events.